Cons. Património 2023
DOI: 10.14568/cp29230
|View full text |Cite
|
Sign up to set email alerts
|

Investigating five totalizing counters manufactured by the Alphonse Darras company of the CNAM collections in Paris

Abstract: The paper reports the study of five totalizing counters preserved in the collections of the CNAM (museum of the French National Conservatory of Arts and Crafts) in Paris. These artefacts are part of a corpus of over forty counters attributed to the Darras company founded by engineer Alphonse Darras (1860-1936). In the framework of the LacCA project at Haute Ecole Arc, Neuchâtel (Switzerland), dedicated to the characterization of lacquered copper-alloys, our attention was drawn to the different aspects of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The use of shellac as a component of surface finishes on technical heritage and decorative brass objects has been confirmed by non-invasive analysis campaigns conducted by FTIR on scientific instruments, technical objects and gilded bronzes dating from the 18th and 19th centuries [4,6]. FTIR analysis of lacquers dating from the 19th and the very beginning of the 20th century also showed that alcohol-based resin lacquers with shellac as a single component were used [7,8]. Unbleached shellac varnishes, exhibiting a bright to dark orange fluorescence under UV illumination, were frequently observed on various objects, both scientific and decorative, during analysis campaigns [9].…”
Section: Introduction 1lacquered Brass Objectsmentioning
confidence: 99%
“…The use of shellac as a component of surface finishes on technical heritage and decorative brass objects has been confirmed by non-invasive analysis campaigns conducted by FTIR on scientific instruments, technical objects and gilded bronzes dating from the 18th and 19th centuries [4,6]. FTIR analysis of lacquers dating from the 19th and the very beginning of the 20th century also showed that alcohol-based resin lacquers with shellac as a single component were used [7,8]. Unbleached shellac varnishes, exhibiting a bright to dark orange fluorescence under UV illumination, were frequently observed on various objects, both scientific and decorative, during analysis campaigns [9].…”
Section: Introduction 1lacquered Brass Objectsmentioning
confidence: 99%